(3QSGdI aj GdCdbGHs
(3ChdgG (B:s
(3gPg hQbGJ ai GdCdbGH GdJi EUWdM GdfGS YdjgG hCLQhgG eLQi GdCeQ GddGRe , heGjJUd HgG hjVGa EdjgG ef GdJQGLe s
(3BNQgG (B:s
(3hdjS HYO gPg GdQJH eeG jJYdb HJQGLe GdfSGA ZjQ GdGSe NGUI Je GdcJGH HYhf Gddg GdhgGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCSJGP GdOcJhQ GSMGb ehSi GdMSjfi GdNGUI s
Keywords: (3Gdabg GdTGaYjs